Clinical Studies on Ropivacaine and Lignocaine for Proximal Paravertebral Anaesthesia in Bovines - Barot, Hiren M.; Patel, Purushhottambhai B.; Sodagar, Bhairavi N.; Patel, Atul M.; Patel, Abhishek M.; Patel, Jignesh B. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Paravertebral anaesthesia is one of the most popular, safe and convenient regional anaesthetic technique in ruminants for flank region surgery in standing position. To evaluate anaesthetic effects of ropivacaine and lignocaine hydrochloride, total 18 bovines were randomly divided in three equal groups. In group I and II animals paravertebral anaesthesia was induced using 0.5 % and 0.75 % ropivacaine, respectively, while in group III, 2 % lignocaine was administrated in paravertebral space. The anaesthetic parameters such as onset of analgesia, duration of analgesia, skin temperature of anaesthetized and contralateral non-anaesthetized site, assessment of analgesia and development of scoliosis were recorded in all three groups. Significantly (p
Keywords: Bovines; Lignocaine; Paravertebral anaesthesia; Ropivacaine; Skin temperature; Scoliosis